Recoletos de Bacolod Graduate School Docuware: E-Document Management System - Mariano D. Antenor, Jr.; Jake R. Pomperada (Philippine Social Science Journal, 2025)
To modernize administrative workflows and address inefficiencies in manual record-keeping, the Recoletos de Bacolod Graduate School (RBGS) developed a tailored Electronic Document Management System (EDMS) using the Rapid Application Development (RAD) methodology. Built with Laravel and MySQL, the system was designed to centralize, digitize, and secure academic documents while ensuring regulatory compliance. Performance testing with 30 faculty and students yielded excellent satisfaction ratings, validating the system’s effectiveness in enhancing accessibility, encryption, and operational efficiency. Although the current iteration lacks version control, the system successfully reduces paper usage and supports accreditation standards. Future enhancements should prioritize integrating version control, AI-driven search algorithms, and cloud-based scalability to further optimize institutional data management.